Pelatihan Aplikasi Mendeley Sebagai Manajemen Referensi bagi Mahasiswa Peserta Magang dan Studi Independen Bersertifikat - Neva Satyahadewi; Warsidah Warsidah; Ilhan Nail Nabil (Indonesian Journal Publisher, 2024)
Compiling a list of references is often an obstacle in completing a scientific work, which then presents applications that can help with this problem. Mendeley software is one of the many applications that is very helpful in compiling a list of citations in a scientific work. It is a very popular application or software with millions of users in academic circles. The large number of students who do not know and understand this application has encouraged Mendeley application training activities for MSIB student participants at the Papua Central Statistics Agency. This activity aims to improve the ability of MSIB participating students in compiling a list of references or references in writing written work. The activity was attended by 28 students from various study programs from various universities throughout Indonesia. This training activity was carried out over 2 days and used lecture, discussion and practice methods. From the results of the activity evaluation through reviewing written work using the Mendeley application, it shows that all participants were able to write written works using the Mendeley application as a reference manager. On the first day the percentage of participants' ability when operating the application was only 36%, then after training on the second day the percentage increased to 100% or all participants were able to understand the use of the Mendeley application due to direct practice in using the application, thereby providing participants with an understanding of both theory, practice and discussions held during the training.